Economic Growth and Income Disparity between Regencies/Cities in West Java Province - S. Lestari; Ratna Setyawati Gunawan (EKO-REGIONAL, 2017)
The aim of this research is to find out the correlation between economic growth and inter regency income disparity in West Java Province year 2005 to 2014. This research is analysis of secondary data, using GDRP Based on constant price 2010, economic growth, and total population year 2005 to 2014. Data obtional from SCA of West Java Province and also the Local Goverment. Analysis model used is Williamson Index, Entropi Theil Index Calculation, Product Moment Colerration Analysis by Pearson, and Trend analysis. Based on Calculation of Williamson Index and Entropi Theil Index inter regency income disparity in West Java Province considered in high disparity with the average of Williamson index by 0.628 and Entropi Theil Index by 1.421. Based on Trand analysis disparity income show increasing trand. The Kuznets Hypothesis (U-inverted curve) proved to be not applicable in West Java Province during 2005 to 2014, and it shows that inequality is getting worse.Keywords: Income Disparity, Economic Growth, Kuznets Hypothesis.